9x - y = -2 Part A. To find the solutions that satisfy the equation, find the corresponding values of y for each given value of x.
Part B. Let x = -3, 9(-3) - y = -2 y = -27 + 2 = -25 Let x = 0, 9(0) - y = -2 y = 2 Let x = 3, 9(3) - y = -2 y = 27 + 2 = 29 Therefore, three different solutions are (-3, -25), (0, 2), (3, 29)
Part C. Pairing the equation with 18x - 2y = 5 will result in a system of equations that is inconsistent.
Free trigonometric identity calculator - verify trigonometric identities step-by-step This website uses cookies to ensure you get the best experience. By using this website, you agree to our Cookie Policy.